2019
DOI: 10.3390/foods8120677
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Gelled Double Emulsions Based on Chia (Salvia hispanica L.) Mucilage Mixed with Different Biopolymers and Loaded with Green Tea Extract (Camellia sinensis)

Abstract: The aim of this research was to develop and characterize five gelled double emulsions based on chia mucilage (CM) and different biopolymers (κ-carrageenan, C; locust bean gum, L; thixogum, T; and whey protein concentrate, W) loaded with green tea extract (GTE). Gelled double emulsions consisted of W1 (whey-protein-concentrate/sodium-azide/NaCl/GTE)/O and (PGPR/canola-oi)/W2 (CM, CMC, CML, CMT and CMW), and were characterized based on physicochemical properties during 35 days of storage. Optical microscopy clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…The simultaneous use of QP and alginate could be an interesting way to stabilize oil droplets by entrapping them into a dense gelled network which improves mechanical and steric stability of EG systems. Similar results were reported in gelled double E formulated with canola oil, whey proteins, chia mucilage, and different biopolymers: after 35 days of storage, there was no phase separation 7 …”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The simultaneous use of QP and alginate could be an interesting way to stabilize oil droplets by entrapping them into a dense gelled network which improves mechanical and steric stability of EG systems. Similar results were reported in gelled double E formulated with canola oil, whey proteins, chia mucilage, and different biopolymers: after 35 days of storage, there was no phase separation 7 …”
Section: Resultssupporting
confidence: 86%
“…4 Recently, plant-derived proteins are being used not only as a possible option to substitute animal sources in the human diet, but also as value-added ingredients for food development. 5 Even though vegetable proteins from soy, chia, and pea have been used in EG formulation [6][7][8] quinoa proteins (QP) have been sparsely applied in this kind of systems. 9,10 Despite not being as common and widespread as wheat or corn, quinoa (Chenopodium quinoa Willd.)…”
Section: Introductionmentioning
confidence: 99%
“…However, significant differences (p ≤ 0.05) were evidenced in a concentration-dependent manner when FT3-250 was added, and the creaming index was lower than the control without FT3-250. This diminution in the creaming index could be due to the fiber-rich nature of xylan and starch ( 7 ) present in the FT3-250, which help keep the oil droplets separate since the cremation rate is prevented by adding thickening agents such as gums or polysaccharides to reduce the movement of the drops ( 13 , 28 , 29 ). It is demonstrated that O/W emulsions with low pseudoplasticity ( n ≈ 1) and low viscosity (low k value) promote creaminess ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although double emulsions show significant potential for improving the fat content of meat products, providing bioactive substances, and disguising odors, their poor stability limits their application. During storage, double emulsions may exhibit creaming, phase inversion, phase separation, flocculation, and coalescence [120]. Gelation is a feasible method for improving stability [121,122].…”
Section: Examination Of the Gelled Double Emulsion As A Fat Substitutementioning
confidence: 99%
“…Biopolymers, such as polysaccharides, can stabilize the emulsion interface by adding them to the continuous phase, allowing their W 2 to form a gel network that prevents creaming and coalescence, consequently improving the stability of double emulsions during storage (Figure 2) [125]. Gelled double emulsions are applied to encapsulate phenolic substances, such as green tea extract and Hxt [117,120], and can be used as fat replacers in meat products. However, minimal studies are available on this topic.…”
Section: Examination Of the Gelled Double Emulsion As A Fat Substitutementioning
confidence: 99%